A Quantitative Study to Assess The Mastery Regarding Breast Feeding among Primi Mothers - Sreelekshmi G S; Shyni J.R.; Sajna V.S; Lida Antony (International Journal of Midwifery Nursing And Practices, 2023)
Background: The study aim to assess the mastery of breastfeeding among primi parous mothers who were admitted to a medical college hospital in Wayanad. Material and methods: This study employed a non-experimental quantitative research methodology, and it involved the selection of 120 primiparous women through purposive sampling. The setting of the study was at DM WIMS the research design was an experimental research design (post-test only control design). The target population of the study is the total number of mothers admitted to the antenatal ward and coming for consultation in the OPD. Results: Analyzing the knowledge scores of 120 samples, 2.5% of mothers have poor knowledge of breastfeeding, 80.83% of mothers have average knowledge of breastfeeding, and 16.6% of mothers have good knowledge.
Keywords: Assessment; Breastfeeding; Knowledge; primi mothers